KAJIAN YURIDIS LARANGAN ADANYA IKATAN PERKAWINAN TERHADAP SESAMA PEKERJA DALAM SATU PERUSAHAAN - I Wayan Agus Vijayantera (Jurnal Analisis Hukum, 2018)
Prohibition of marriage ties to fellow workers is formed by employers to maintain professional attitudes of workers in carrying out the work. Article 153 Paragraph (1) Sub-Paragraph f of the Law of the Republic of Indonesia Number 13 Year 2003 when viewed proves to provide a loophole for employers to prohibit the existence of marriage bonds between fellow workers established in employment agreements, company regulations, and collective labor agreements. Based on this matter, it is necessary to conduct a juridical study with the aim to know the causes of the prohibition of marriage bonds against fellow workers in the company and the prohibition of marriage bonds among fellow workers in a company is reviewed in the perspective of law of agreement. In the discussion, after the Decision of the Constitutional Court Number 13/PUU-XV/2017, the employer is not allowed to prohibit the bonds of fellow workers in his company because they are contradictory to the 1964 Constitution of the State of the Republic of Indonesia in particular against the Human Rights. The rules that prohibit the existence of such fellow marriage bonds are reviewed in the treaty law, they can not be based on the principles of contract law. Based on that, the rules should be established by employers is a rule that requires workers to be professional in the work, not by prohibiting workers have marital ties.Keywords: Prohibition, Marriage, Workers.